The motivational mechanism behind college students’ willingness to participate in rural revitalization–a case study of the “Furong Scholars •Rural Revitalization” public welfare program in Hunan Province, China - Zhou, Rongji; Chen, Bin (Frontiers in Psychology, 2025)
Grounded in the Theory of Planned Behavior (TPB), this study develops a framework comprising five core constructs: rural revitalization cognition, behavioral attitude, subjective norm, perceived behavioral control, and willingness to participate. Drawing on the “Furong Scholars • Rural Revitalization” program in Hunan, China, we surveyed 634 college students and employed SEM, mediation analysis, and DEMATEL to explore the micro-level motivational mechanisms influencing their participation willingness. The key findings are as follows: (1) Individual and social factors significantly affect willingness to participate. Female students, those with urban household registration, humanities and social sciences majors, students with higher academic qualifications, and those with stronger political consciousness exhibit greater willingness to participate. (2) Rural revitalization cognition is central to the motivational system as a strong causal factor (centrality = 1.115), positively influencing behavioral attitude, subjective norm, perceived behavioral control, and participation willingness. (3) Behavioral attitude (p < 0.05), subjective norm (p < 0.001), and perceived behavioral control (p < 0.001) all significantly enhance willingness to participate, with subjective norm and perceived behavioral control showing stronger path effects. Moreover, these three variables act as key mediators between rural revitalization cognition and willingness to participate, forming crucial motivational pathways. These findings deepen the theoretical understanding of college students’ behavioral motivations in the context of rural revitalization and offer empirical insights for designing more targeted and effective policy interventions. Specifically, enhancing students’ cognition of rural revitalization, strengthening social normative support, and improving self-efficacy are identified as vital levers for increasing their willingness to engage in rural development initiatives.